O papel da imaginação no conhecimento humano segundo David Hume - Alves, Marcelo de Sousa Ferreira (2015)
This dissertation offers an account of the relation of the faculty of imagination whith the formation of belief and with other faculties such as memory and understanding in Hume’s thought. The main focus of the investigation is the work Treatise on Human Nature, nonetheless some considerations will be made about the contribution of the work Investigation on Human Understanding to the topic at stake. This is a work purported to show that the imagination has a fundamental role in the reasoning processes about the work and about the empirical sciences.